Should I go to grad school? : - Loudis, Jessica. (Bloomsbury, 2014)
The decision to attend graduate school is easy for future doctors and lawyers: they must have a professional degree to get started. But for young creative workers, aspiring artists, and intellectuals, grad school is an existential fork in the road. An M.F.A. or a humanities Ph.D. can give you time to invest in studying something you love among like-minded intellectuals and qualify you to teach a new generation of students; but it can also uproot you geographically, expose you to backstabbing competitors, and saddle you with debt. Given the current job market, is grad school really worth it-financially, professionally, and emotionally?